Persistência de dividendos e gerenciamento de resultados em mercados de capitais da América Latina - Sousa, Raíssa Aglé Moura de (2017)
This work aims to investigate the relationship between dividend persistence and earnings management in open companies of Latin American capital markets. Based on Relevance of Dividend Theory and Bird in the Hand Theory (LINTNER, 1962; GORDON, 1963), a theoretical framework was developed to discuss dividend persistence as well as previous studies about earnings management. To meet the general and specific objectives four quantile regression models in quartiles were estimated, since heteroskedasticity problems was identified on the sample and this type of regression has robustness to these problems. Among the models, the one of Lintner (1956) highlights, which was used interacting with earnings management (discretionary accruals), that was estimated using Dechow et al. model (2012). The sample research is composed by 1,532 company/year observations, equal to the total of 364 companies, for the period from 2001 to 2015. As the mains results of this research, it was verified that the Dividend Payout of the companies is not influenced by the level which the companies manage their results, but is influenced by the variables of return on equity, by the opportunity of growth (market-to-book), by indebtedness and the size of the companies, depending on the quartile analyzed. Regarding the analysis of dividend persistence, it was verified that the payouts of the companies are persistent in all quartiles analyzed. It was also proven, according to one of the research hypotheses that in the presence of a higher level of earnings management the payouts are more persistent. However, this result was evidenced in the enterprises that distribute the most dividend (quartiles 0.50 and 0.75), since in the companies that distribute lower volume of dividends (quartile 0.25) this hypothesis was refuted. Thus, it can conclude that there are indications of dividend persistence in the Latin American open market companies that most manage results.